Pengaruh Penambahan Ekstrak Andaliman terhadap Masa Simpan Nugget Tempe - Daniela, Connie (Jurnal Riset Teknologi Pangan dan Hasil Pertanian (RETIPA), 2020)
Andaliman  is  typical spice plant in North Sumatra, has benefits as antimicrobial and antioxidant. Tempeh is a protein source food, has short shelf life, so the tempeh processing technology is needed to create another product with  longer shelf life and increase its added value. One of them is by processing tempeh into nugget. The purpose of this study was to determine the shelf life of tempeh nugget added with andaliman fruit extract as  natural preservative and to determine which concentration was the most optimal in extending the shelf life of tempeh nugget. This study used  completely randomized design with two factors. Factor I was the concentration of andaliman extract (0%, 0.1%, 0.25%, 0.5%) and factor II was the storage time (0 day, 7 days, 14 days, 21 days). The parameters analyzed were total microbial, water content, and aroma organoleptic test. The results showed that the addition of 0.5% andaliman extract and 21 days storage time obtained the lowest amount of microbes, the lowest water content was obtained at 0% andaliman extract and 21 days storage time treatment, while the highest aroma organoleptic test was obtained at adding 0.5% andaliman extracts. This is due to the presence of antimicrobial in andaliman